Public Knowledge and Attitude toward Essential Tremor: A Questionnaire Survey - Shalaby, Sherif; Indes, Jeffrey; Keung, Benison; Gottschalk, Christopher H.; Machado, Duarte; Patel, Amar; Robakis, Daphne; Louis, Elan D. (Frontiers in Neurology, 2016)
Background: Public awareness of and attitude towards disease is an important issue for patients. Public awareness of essential tremor (ET) has never been studied. Methods: We administered a ten-minute, 31-item questionnaire to 250 consecutive enrollees. These included three samples carefully chosen to have a potential range of awareness of ET: 100 individuals ascertained from a vascular disease clinic, 100 individuals from a general neurology clinic, and 50 Parkinson’s disease (PD) patients. Results: Leaving aside PD patients, only 10-15% of enrollees had ever heard of or read about “ET”. Even among PD patients, only 32.7% had ever heard of or read about ET. After providing enrollees with three synonymous terms for ET (‘benign tremor’, ‘kinetic tremor’, ‘familial tremor’), approximately 40% of non-PD enrollees and 51.0% with PD had ever heard or read about the condition. Even among participants who had heard of ET, approximately 10% did not know what the main symptom was, 1/3 were either unsure or thought ET was the same disease as PD, 1/4 thought that ET was the same condition as frailty- or aging-associated tremor, 2/3 attributed it to odd causes (e.g., trauma or alcohol abuse), only 1/3 knew of the existence of therapeutic brain surgery, fewer than 1/2 knew that children could have ET and 3/4 did not know of a celebrity or historical figure with ET. Hence, lack of knowledge and misconceptions were common. Conclusions: Public knowledge of the existence and features of ET is overall poor. Greater awareness is important for the ET community.